Language Barriers in Primary School English Classes in Baku Private Schools - Kalbiyeva, Sabina; Bayramova, Leyla; Bakhishova, Nuriya (My University, 2026)
Language barriers can affect students’ participation and learning in English classes, especially in primary school. This study explored English teachers’ perceptions of language barriers in private primary schools in Baku and the strategies they use to overcome these challenges. The study followed a qualitative research design within an interpretive paradigm. Data were collected through semi-structured interviews with nine primary English teachers working in private schools in Baku. The findings showed that students face three main types of barriers: linguistic, psychological, and organisational. The linguistic barriers included problems with oral skills, vocabulary, sentence building, first-language influence, and comprehension. Psychological barriers included fear of mistakes, low self-confidence, shyness, and anxiety. The organisational barriers included lack of lesson time, mixed-ability classes, large class sizes, curricula pressure and limited parental support. Teachers reported using a range of strategies to address these barriers. These strategies included interactive speaking activities, games, role plays, scaffolding, visual aids, vocabulary support, differentiation, and creating a positive classroom environment where students feel comfortable making mistakes. The study contributes to a better understanding of English language teaching in private primary schools in Baku and offers practical recommendations for teachers, schools, and future research.
Keywords: Language barriers; English language teaching; Primary school; Teachers’ perceptions; Private schools